Nepali Communist Parties in Elections: Participation and Representation - Shrestha, Amrit Kumar (Dristikon: A Multidisciplinary Journal, 2020)
The communist parties are not gaining popularity throughout the countries of the world, as they are shrinking. The revolutionary communist forces are in a defensive position, and the reformist communists have failed to achieve good results in the elections. Communist parties are struggling just for their existence in the developed countries. They are not in a decisive position, even in developing countries as well. Nevertheless, communists of Nepal are obtaining popularity through the elections. Although the communists of Nepal are split into many factions, they have been able to win the significant number of seats of electoral offices. This article tries to analyze the position of communist parties in the general elections of Nepal. It examines seven general elections of Nepal held from 1959 to 2017. Facts, which were published by the Elections Commission of Nepal at different times, were the basic sources of information for this article. Similarly, governmental and scholarly publications were also used in the article.